2016
DOI: 10.1007/s13205-016-0368-z
|View full text |Cite
|
Sign up to set email alerts
|

Insight into thermophiles and their wide-spectrum applications

Abstract: The deconstruction of biomass is a pivotal process for the manufacture of target products using microbial cells and their enzymes. But the enzymes that possess a significant role in the breakdown of biomass remain relatively unexplored. Thermophilic microorganisms are of special interest as a source of novel thermostable enzymes. Many thermophilic microorganisms possess properties suitable for biotechnological and commercial use. There is, indeed, a considerable demand for a new generation of stable enzymes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(49 citation statements)
references
References 79 publications
0
44
0
1
Order By: Relevance
“…Instead, each biomolecule inside microorganisms must be adapted to the temperatures in which they grow. This makes proteins and metabolites from microbes growing at hot temperatures particularly interesting for biotechnological and industrial applications [ 8 ]. Organisms can be generally categorized based on the temperature range of their optimal growth.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, each biomolecule inside microorganisms must be adapted to the temperatures in which they grow. This makes proteins and metabolites from microbes growing at hot temperatures particularly interesting for biotechnological and industrial applications [ 8 ]. Organisms can be generally categorized based on the temperature range of their optimal growth.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, each biomolecule inside microorganisms must be adapted to the temperatures in which they grow. This makes proteins and metabolites from microbes growing at hot temperatures particularly interesting for biotechnological and industrial applications (Mehta et al 2016) . Organisms can be generally categorized based on the temperature range of their optimal growth.…”
Section: Introductionmentioning
confidence: 99%
“…Also, there are many factors affecting the tolerance level of thermophilic bacteria, these include; permeability, chemical stability of membrane lipids and GC contents. Similarly, there are more hydrogen bonds in GC base pair compared with AT base pair (Mehta et al 2016). In addition, the pH observation showed that the sampling locations have neutral pH.…”
Section: Discussionmentioning
confidence: 95%